Micro-magnetic non-destructive characterization of multi-clad array coating of FeCoCrNiMo high entropy alloy in laser cladding - Diwakar V.; Sharma A.; Khan Yusufzai M.Z.; Vashista M. (My University, 2025)
This paper highlights the potential of NDT approach i.e., micro-magnetic barkhausen noise (MBN) and hysteresis loop (HL) techniques to assess the complex microstructural and mechanical characteristic of multi-coating FeCoCrNiMo high entropy alloy over inadequate EN24 steel using laser cladding. To analyze the trends of the micro-magnetic responses, magnetic frequency and magnetic field intensity as input factors are varied. The obtained micromagnetic responses, i.e., peak, RMS, average permeability, coercivity, and remanence linearly correlated with the microstructural aspect i.e. grain size, microhardness, and XRD-FWHM of the cladded, interface, and substrate region and its correlational coefficient lie in range of ∼0.9350 to 0.9942, ∼0.8996 to 0.9793, ∼0.8464 to 0.9927, ∼0.8464 to 0.9927, ∼0.8433 to 0.9766, and ∼0.8255 to 0.9674, respectively. Post processing of magnetic signals indicated the negligible MBN peak shifting with narrow envelope and limited saturation level of HL envelope was observed in cladded zone as followed by substrate caused by uniform grain refinement (∼9 μm) along with higher microhardness (470 HV) and XRD-FWHM (0.76) and complex multiphase distribution under controlled laser processing. It is confirmed that MBN and HL techniques provides the quick and reliable response of additively coated HEA's on-line production. © 2025 Elsevier Ltd